New Emphasis on Water Transparency as Socio-Ecological Indicator for Urban Water: Bridging Ecosystem Service Supply and Sustainable Ecosystem Health - Teubner, Katrin; Teubner, Irene; Pall, Karin; Kabas, Wilfried; Tolotti, Monica; Ofenböck, Thomas; Dokulil, Martin T. (Frontiers in Environmental Science, 2020)
The perspective on water transparency changed since the early days of limnology from being a physical parameter of optical water property to an ecological indicator tracking algal turbidity due to eutrophication or an overall success of sustained lake restoration in the late 60ies to 80ies. In modern cities, where ecosystems are commonly deteriorated by man-made modifications, water transparency offers a great opportunity to the public to raise socio-ecological consciousness concerning urban green-blue spaces. We thus re-emphasise water transparency as a key indicator of multi-functional value when assessing an oxbow lake of the riverine floodplain in Vienna, the Alte Donau. Our study covers the eutrophication from 1987-1994 due to the inclusion of the riverine landscape in the urban area, the following lake restoration with an ecosystem shift from a nutrient-rich, algal-turbid water body to a nutrient-poor, clear-water macrophyte controlled system and the impact of global warming in recent decades. We used light attenuation profiles to identify depth layers of specific ambient light requirements for photosynthetic domains (phytoplankton and submerged macrophytes), and to interpret Secchi measurements. Here we calculated the depth at 1% (minimum light requirements for phytoplankton growth as euphotic depth), 3% (minimum light requirements for macrophytes as maximum macrophyte colonization depth) and 12% (preferred light requirements for phytoplankton development) of surface ambient light. A Secchi disk water transparency of 1.5m (“lake bottom view”), judged as good water quality by human perception, refers to mesotrophic conditions with a maximum colonization depth for macrophytes exceeding the mean lake depth in Alte Donau. Water clarity required for sustained macrophyte growth, in particular for favouring bottom-dwelling Chara meadows instead of tall-growing Myriophyllum spicatum, is 3.5m Secchi depth and thus exceeds by far water clarity requested due to bathing aesthetics. Global warming, mirrored by an advanced warming in spring seems to favor significantly a higher yield of macrophytes mainly built up by Myriophyllum at the expense of the yield of algae. The prolongation of the summer period above 21°C, however, coincides with lowered Secchi transparency. Water visibility during the hot season thus seems to be slightly hampered against lake restoration efforts by global warming.